2007
DOI: 10.1117/1.2816459
|View full text |Cite
|
Sign up to set email alerts
|

Limiting factors for electron beam lithography when using ultra-thin hydrogen silsesquioxane layers

Abstract: Abstract. Isolated dots and lines with 6 nm width are written in 20-nm-thick hydrogen silsesquioxane ͑HSQ͒ layers on silicon substrates, using 100-keV electron beam lithography. The main factors that might limit the resolution, i.e., beam size, writing strategy, resist material, electron dose, and development process, are discussed. We demonstrate that, by adjusting the development process, a very high resolution can be obtained. We report the achievement of 7 nm lines at a 20-nm pitch written in a 10-nm-thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The main risk of using a strong developer when writing nanostructures is that the structures may be washed away and only highly exposed areas remain on the substrate. This effect has been suggested by Grigorescu et al [72] when writing arrays of 6 nm dots in a 20 nm HSQ resist layer using two different concentrations of TMAH developer. MF-322 was used undiluted (N = 0.268 eq l −1 ) and diluted with demineralized water in a ratio 1:3 (N = 0.067 eq l −1 ).…”
Section: Development Processmentioning
confidence: 60%
See 4 more Smart Citations
“…The main risk of using a strong developer when writing nanostructures is that the structures may be washed away and only highly exposed areas remain on the substrate. This effect has been suggested by Grigorescu et al [72] when writing arrays of 6 nm dots in a 20 nm HSQ resist layer using two different concentrations of TMAH developer. MF-322 was used undiluted (N = 0.268 eq l −1 ) and diluted with demineralized water in a ratio 1:3 (N = 0.067 eq l −1 ).…”
Section: Development Processmentioning
confidence: 60%
“…Grigorescu et al [72] reported a recipe to obtain ultrathin HSQ resist layers. By using a higher dilution rate, 1:10 FOx-12:MIBK, a 10 nm thick HSQ layer was obtained at 3000 rpm for 60 s on a Karl Suss spinner with the lid closed (in order to decrease the rate of evaporation of the solvent) (see figure 20).…”
Section: Spin Coating Of Resistmentioning
confidence: 99%
See 3 more Smart Citations